WSP from “Nostoc commune” Vauch. suppresses gastric cancer migration via EGFRVIII signaling - Chen, Xiaoxia; Bai, Wenqi; Liu, Xiangrong; Zhao, Jiao; Li, Zhiyuan; Li, Jianrong; Su, Liping; Guan, Tao; Sun, Ruifang; Yang, Xihua; Lv, Caixia; Wang, Zhixiang; et al. (Frontiers in Oncology, 2022)
A number of evidences have proved that “Nostoc commune” Vauch can improve human immunity and prevent diseases, however, the specific mechanism remains unclear. The biological activity of the main protein component of “Nostoc commune” Vauch extracellular matrix– a water-stress protein (WSP) still needs to be elucidated. Here we found that WSP can significantly inhibit the metastasis of gastric cancer cells. Moreover, the anti-metastasis activity of WSP was recapitulated in the xenograft GC cancer model in vivo. Interestingly, we found that the anti-metastasis ability of WSP on gastric cancer was related to membrane protein receptor EGFRVIII, which was realized by inhibiting the downstream EGFRVIII signaling pathway. In terms of mechanism, WSP can inhibit the downstream EGFRVIII signaling pathway Akt-PI3K and further inhibit the secretion of cancer-related metastasis proteins such as MMP2 and MMP9, thus, significantly affecting the metastasis of gastric cancer cells.